Learning Management System Usage and English Learning Motivation: Evidence from a Simple Linear Regression Study - Aam Amaliah; Heny Fitriani; Rosdiana; R. Dewi Mutia Farida; Fitriani Yuniar (Jurusan Teknik Informatika dan Komputer, 2025)
The integration of Learning Management Systems (LMS) has become an essential component of English language instruction in higher education, particularly in vocational contexts. However, empirical evidence explaining how LMS usage influences students’ learning motivation remains limited. This study aims to examine the effect of LMS usage on students’ motivation in learning English using a quantitative explanatory approach. The study involved 120 vocational higher education students enrolled in English courses, selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS. The results indicate that LMS usage has a significant positive effect on students’ English learning motivation (β = 0.484, p < 0.001), with an R² value of 0.318, suggesting that LMS usage explains 31.8% of the variance in learning motivation. These findings demonstrate that structured LMS features, interactive content, and timely feedback contribute meaningfully to students’ motivational engagement in English learning. This study provides empirical evidence that LMS functions not only as a digital learning platform but also as a motivational driver in vocational English education, offering practical implications for instructors and institutions in designing effective LMS-supported learning environments.